Financial openness for small open economy / Nur Asyiqin Ramadhan and Tay Bee Hoong - Ramadhan, Nur Asyiqin; Tay, Bee Hoong (2012)
The openness declared in Malaysia aims to strengthen the economic interlink-ages with other economies and enhancing the role of the liberalization itself as a key enabler and mechanism of economic growth. The main concern of this study is to examine the correlation between financial openness towards economy and the total output growth. Primary attention has been given, for not just focusing on country level but also going in depth into industry level to look at this relationship based on Malaysia experience. The emergence of this study is due to the highly debated topic since the liberalization is announced and due to the mix result on the effect of financial openness towards growth by past researchers in different cross-country. Besides, most literatures on financial openness are based on the economic growth at country level and only few in industrial level. Thus, this paper attempts to seek the relation of the financial openness proxy by de facto (the volume of a country's foreign asset and liability) and de jure (index of capital account openness) towards the Malaysia economy as a whole and more specific to industrial level which is manufacturing. Different measurement of financial openness used since it is arguably by previous researchers on both indexes. The relevancy of selecting manufacturing industry in this research is because it has a dominant force in the Malaysian growth experience, contributing significantly to growth of output. By looking at the manufacturing industry, this study adopted Pearson Correlation and OLS Regression to meet the objectives of the research. In addition, the empirical work had extended towards Granger causality test to have a reverse relationship on variables. The study used time series data ranges from 1970 to 2007. The proxy for financial openness data derived from Chin and Ito (2009) for de jure while Milesi-Feretti (2006) for de facto. The study shows mixed result on both proxies which are de jure and de facto towards the economy and industry. In Granger causality test, the finding shows financial openness is the one that give impact to the both economy and industry in Malaysia. This finding can be concluded that financial openness enhances growth regardless of their characteristics.